Practice in industry training in fish technology. - Lero, Marisa C. (College of Fisheries, University of the Philippines in the Visayas, 1997)
The college of Fisheries, University of the Philippines requires its students and prospective graduates to undergo training in the different establishments either privately owned or government owned. The aim of the college is to enable the students to apply the theories and principles they have learned in the classroom and at the same time, to make them aware of the problems, the development, and the potential of the industry.